Risk Management of the Free Nutritional Meal Program: Financial, Health, Social Perspectives - Ach Mezzaluna Rizky Irwinsyah; Sundjoto Sundjoto; Sri Rahayu (Universitas KH. Abdul Chalim Mojokerto, 2026)
The Free Nutritional Meals (MBG) Program is a strategic government policy aimed at improving the quality of human resources through nutritional interventions. However, the complexity of budget management, food distribution, and the involvement of various stakeholders makes this program vulnerable to various risks. This study aims to analyze the implementation of risk management in the MBG Program from a financial, health, and social perspective, and its impact on financial performance and program sustainability. The study used a descriptive qualitative approach using interviews, observation, and documentation. The analysis was conducted based on the ISO 31000:2018 framework. The results indicate that the implementation of integrated risk management can improve budget efficiency, maintain food safety, and strengthen the program's social legitimacy. Risk management positively contributes to financial performance through increased transparency, accountability, and waste control. Furthermore, effective risk management supports program sustainability through funding stability and increased stakeholder trust. This study emphasizes the importance of integrating risk management in the governance of nutrition-based social programs.